Inkjet Printed SnO2 Gas Sensor on Plastic Substrate. (2015) - Rieu, M.; Camara, M.; Tournier, G.; Viricelle, J.P.; Pijolat, C.; de Rooij, N.F.; Briand, D.
Abstract: We report on the development of a metal oxide (MOx) sensor prepared by inkjet printing technology onto polyimide foil. Gold electrodes and a gold heater were printed on each side of the substrate, respectively. SnO2 based ink was developed by sol-gel method and printed onto the electrodes. A final annealing at 400 °C compatible with the polymeric transducers allows to synthetize the SnO2 film. Electrical measurements were carried out to characterize the response of fully printed sensor under different gases. The device was operated at a temperature between 200 and 300 °C using the integrated heater. The sensor exhibited responses to carbon monoxide and nitrogen dioxide, under dry and wet air.